NetGuardians: Lightweight Serious Game for Cybersecurity Education - Tan, Tony; Jong, Ricky; Febrianto; Wibowo, Tony (Journal of Games, Game Art, and Gamification, 2026)
This paper presents NetGuardians, an interactive narrative-driven serious game designed to support cybersecurity awareness among high school students. As cybersecurity threats continue to increase, particularly affecting young learners, there is a growing need for engaging educational approaches that can introduce essential digital security concepts in an accessible manner. NetGuardians focuses on three fundamental topics: recognizing phishing attacks, promoting strong password practices, and understanding the risks associated with public Wi-Fi usage. The game was developed using the Game Development Life Cycle (GDLC) methodology and integrates storytelling, interactive quizzes, and real-life case scenarios. In addition, a comparative analysis was conducted with existing cybersecurity educational games, including Riskio, CyberHero, and CSRAG, to examine differences in content focus, engagement strategies, and academic design approaches. To explore students' learning experiences, qualitative data were collected through interviews with 25 high school students. The interview questions, based on concepts from serious games and game-based learning literature, focused on perceived learning, engagement, cybersecurity awareness, and digital decision-making. The qualitative findings suggest that participants reported increased cybersecurity awareness, especially regarding phishing and password security, and found the narrative and interactive elements helpful in understanding the material. However, due to the qualitative nature of the study and the lack of empirical learning measurements, the educational impact remains inconclusive. The study concludes that NetGuardians shows potential as a narrative-based tool for cybersecurity education, but further development and quantitative evaluation are needed to confirm its effectiveness.